2008
DOI: 10.1158/1535-7163.mct-07-0428
|View full text |Cite
|
Sign up to set email alerts
|

Fasudil-induced hypoxia-inducible factor-1α degradation disrupts a hypoxia-driven vascular endothelial growth factor autocrine mechanism in endothelial cells

Abstract: Hypoxic response of endothelial cells (EC) is an important component of tumor angiogenesis. Especially, hypoxiainducible factor-1 (HIF-1) -dependent EC-specific mechanism is an essential component of tumor angiogenesis. Recently, the Rho/Rho-associated kinase (ROCK) signaling has been shown to play a key role in HIF-1A induction in renal cell carcinoma and trophoblast. The present study was designed to investigate whether low oxygen conditions might modulate HIF-1A expression through the Rho/ROCK signaling in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 46 publications
6
37
0
Order By: Relevance
“…In the tumor microenvironment, hypoxia can cause some effector cells to produce HIF-1␣, which is the upstream regulatory gene of VEGF (42). VEGF also has been demonstrated to interact with the HIF-1␣ via an autocrine loop (43,44). The level of VEGF and HIF-1␣ could directly and indirectly indicate the ability of a tumor to cause angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the tumor microenvironment, hypoxia can cause some effector cells to produce HIF-1␣, which is the upstream regulatory gene of VEGF (42). VEGF also has been demonstrated to interact with the HIF-1␣ via an autocrine loop (43,44). The level of VEGF and HIF-1␣ could directly and indirectly indicate the ability of a tumor to cause angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…16 It is worth noting that previous reports indicated that RhoA is also a hypoxiatargeted gene that receives responses from HIF-1a/VEGF signaling under hypoxic conditions. 17,18 Combining these results, we hypothesized that RhoA may participate in the hypoxia-induced VEGF signaling through the MDM2-p53 pathway that regulates TNV angiogenesis in human malignancies.…”
Section: Introductionmentioning
confidence: 92%
“…17 Cell lysates were incubated with an anti-p53, anti-RhoA, or anti-MDM2 antibody. The immune complexes were precipitated with protein A-Sepharose or protein G-Sepharose 4B (Amersham Biosciences, Sunnyvale, Calf).…”
Section: Immunoprecipitation and Coimmunoprecipitation Assaysmentioning
confidence: 99%
“…Cell migration is a critical step in the process of angiogenesis (21). Therefore, we evaluated the effects of fasudil treatment on the migration of LCc-ECs using in vitro migration assays.…”
Section: Fasudil Inhibits Lcc-ec Migrationmentioning
confidence: 99%